2018
DOI: 10.1039/c7cp08364e
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of sodium polyphosphates on an iron oxide surface at high temperature

Abstract: Density functional theory (DFT) and first principles molecular dynamics (FPMD) studies of pyrophosphate cluster NaPO and triphosphate cluster NaPO absorbed and decomposed on an FeO(0001) surface have been conducted. Comparative analyses of the structure properties and adsorption processes during the simulation at elevated temperature have been carried out. The results depict the key interactions including the covalent P-O bonds, pure ionic Na-O or Fe-O interactions. The iron oxide surface plays an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 86 publications
3
27
0
Order By: Relevance
“…The chain length also has an influence on the depolymerization behavior. In fact, Na 4 P 2 O 7 indicated no bond breaking for the P-O b bond at 1100 K, while there was a coexistence of bond breaking and reforming during simulation for Na 5 P 3 O 10 on the iron oxide surface [32]. This simultaneous depolymerization and polymerization of phosphate chains from AIMD simulations affirmed the previous XPS experimental characterizations [1].…”
Section: Borate Glasssupporting
confidence: 77%
See 3 more Smart Citations
“…The chain length also has an influence on the depolymerization behavior. In fact, Na 4 P 2 O 7 indicated no bond breaking for the P-O b bond at 1100 K, while there was a coexistence of bond breaking and reforming during simulation for Na 5 P 3 O 10 on the iron oxide surface [32]. This simultaneous depolymerization and polymerization of phosphate chains from AIMD simulations affirmed the previous XPS experimental characterizations [1].…”
Section: Borate Glasssupporting
confidence: 77%
“…Unlike organic phosphite/phosphate additives used in automotive applications, where the direct Fe-P bonding was found on iron surfaces because of the chemical dissociation of phosphite/phosphate under friction, leading to the formation of Fe 2 P [39,40], the AIMD simulations in Figure 4 revealed that the cross-linking with the Fe-O-P bond between phosphate and the iron substrate was the main chemical structure in phosphate glass [31,32]. The Fe-P bond only occurred in a combination of an elevated temperature of 1500 K, a high exposure of Fe, and an appearance of under-coordinated P [33].…”
Section: Phosphate Glassmentioning
confidence: 94%
See 2 more Smart Citations
“…The depolymerization reaction actively accommodates abrasive particles upon which the anti-wear capacity thrives. [13][14][15] On steel pair lubricated by borate, the boron oxides highly concentrates in the form of a compact and robust boundary lm to withstand direct asperity contacts. 7 Although the tribological behaviors of network-forming constituents have been understood in some extent, there remain unanswered questions surrounding the roles of alkali elements in melt lubrication.…”
Section: Introductionmentioning
confidence: 99%